2018
DOI: 10.3389/fcell.2018.00072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Human Sperm Capacitation

Abstract: In the early 1950s, Austin and Chang independently described the changes that are required for the sperm to fertilize oocytes in vivo. These changes were originally grouped under name of “capacitation” and were the first step in the development of in vitro fertilization (IVF) in humans. Following these initial and fundamental findings, a remarkable number of observations led to characterization of the molecular steps behind this process. The discovery of certain sperm-specific molecules and the possibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
195
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(203 citation statements)
references
References 352 publications
(488 reference statements)
5
195
0
3
Order By: Relevance
“…48,49 Cyclic AMP-mediated protein kinase A activation is known to occur during sperm capacitation. 48,49 Cyclic AMP-mediated protein kinase A activation is known to occur during sperm capacitation.…”
Section: Effect Of Fk506 On Protein Phosphorylation During Sperm Camentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 Cyclic AMP-mediated protein kinase A activation is known to occur during sperm capacitation. 48,49 Cyclic AMP-mediated protein kinase A activation is known to occur during sperm capacitation.…”
Section: Effect Of Fk506 On Protein Phosphorylation During Sperm Camentioning
confidence: 99%
“…Increased tyrosine and serine phosphorylation of proteins accompany sperm capacitation. 48,49 Cyclic AMP-mediated protein kinase A activation is known to occur during sperm capacitation. 3 We determined tyrosine and PKA-mediated serine phosphorylation in FK506-treated sperm.…”
Section: Effect Of Fk506 On Protein Phosphorylation During Sperm Camentioning
confidence: 99%
“…Other common targets in somatic cells for both gasotransmitters are the Ca 2+ channels [29,35] and K + channels [29,35,59]. The regulation of Ca 2+ currents in sperm is of particular interest, as CatSper are involved not only in sperm capacitation [109], but also in sperm hyperactivation, acrosome reaction, and chemotaxis [53,110]. The hypothesis of NO involvement in chemotaxis through affection of the ion channel function may seem intriguing, as Miraglia et al [111] observed a positive influence of NO on sperm migration.…”
Section: No and H 2 S Interactionsmentioning
confidence: 99%
“…At ejaculation, spermatozoa stored in the distal portion of the epididymis mix with the accessory glands secretions and are deposited in the female tract, where they undergo a set of complex and coordinated changes to accomplish fertilization (Satouh & Ikawa, ). Spermatozoa undergo capacitation, a process by which they develop full fertilizing potential, as evidenced by their ability to undergo acrosome reaction and to interact with the oocyte vestments (De Jonge, ; Puga Molina et al , ). Several studies have identified MI phosphoderivatives in sperm mechanisms related to these processes, including progressive and hyperactive motility, sperm guidance, sperm capacitation, acrosome reaction, and sperm–oocyte interactions.…”
Section: Myo‐inositol and Derivates In The Male Reproductive Tractmentioning
confidence: 99%